Ag Loading Enhanced Photocatalytic Activity of g-C3N4 Porous Nanosheets for Decomposition of Organic Pollutants - Qi, Kezhen; Li, Yi; Xie, Yubo; Liu, Shu-yuan; Zheng, Kun; Chen, Zhe; Wang, Ruidan (Frontiers in Chemistry, 2019)
The g-C3N4 porous nanosheets with different loading amount of Ag nanoparticles (NPs) are successfully prepared by a simple liquid-phase reduction method. These Ag/g-C3N4 composites have an improved photocatalytic performance for decomposing organic pollutants compared with that of pure g-C3N4 nanosheets. Many measurements have been used for characterizing the samples, such as XRD, FTIR, UV-Vis DRS, PL, XPS, EDS, SEM, and TEM. In Ag/g-C3N4, the Ag NPs are uniformly coated on the g-C3N4 surface, the diameter is mainly in the range of 8 18 nanometers. Loading of Ag NPs expand the response to the visible light for g-C3N4 and increasing the producing rate of photogenerated e−-h+ pairs. The loading of silver NPs obviously enhances the photocatalytic activity of C3N4 nanosheets toward the Rhodamine B (RhB) decomposition under the simulated sunlight irradiation. With different loading amounts of Ag NPs, Ag/g-C3N4 (3 wt% of Ag) showed the highest photocatalytic activity for RhB decomposition among these as-prepared samples, which is 10 times of the rate of pure C3N4. Based on the experimental results, a possible photocatalytic mechanism for Ag/g-C3N4 is proposed.